2015
DOI: 10.33073/pjm-2015-011
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of Campylobacter spp. and occurrence of virulence genes isolated from dogs

Abstract: This study was conducted to determine the prevalence of Campylobacter spp. isolated from dogs' faecal samples. From June 2012 to June 2013, a total of 210 faecal samples from pet dogs living in different kennels (n = 210) were collected by the owners in Greater Poland Voivodeship, Poznań District, Poland. The study revealed that 105 out of 210 faecal samples (50%) contained Campylobacter. The highest prevalence of Campylobacter spp. occurred in spring (81%), followed by winter (64%). The cadF gene was found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 18 publications
2
11
1
1
Order By: Relevance
“…12.6%. This result stood in opposition to our earlier studies [ 1 , 20 ] and research conducted by other authors [ 5 , 21 ]. Chaban et al [ 22 ] analysed a group ( n = 70) of healthy dogs and found bacteria of the Campylobacter genus in 58% of the samples.…”
Section: Discussioncontrasting
confidence: 99%
“…12.6%. This result stood in opposition to our earlier studies [ 1 , 20 ] and research conducted by other authors [ 5 , 21 ]. Chaban et al [ 22 ] analysed a group ( n = 70) of healthy dogs and found bacteria of the Campylobacter genus in 58% of the samples.…”
Section: Discussioncontrasting
confidence: 99%
“…fetus recovered from water and milk samples. In the studies of Lluque et al [ 77 ], Wieczorek et al [ 78 ] and Selwet et al [ 79 ], the cadF gene was detected in Campylobacter species from a Peruvian pediatric cohort, from meat samples and from Campylobacter isolates isolated from dogs and these reports corroborate our finding. The presence of one or more virulence genes in the Campylobacter genome give rise to the incidence of human infection (Abu-Madi et al [ 80 ]).…”
Section: Discussionsupporting
confidence: 90%
“…The other studies reported Campylobacter infection rates of 4.81-51.1%. 5,[22][23][24][25][26][27] The variation in the rate of infection may rely on the sample size, age, diet, and gastrointestinal status (diarrheal or healthy) of the studied dogs, different diagnosis methods, and geographical location, as well as the season of sampling. The most prevalent species of Campylobacter among the dogs were C. coli (38.89%) and C. jejuni (33.33%).…”
Section: Discussionmentioning
confidence: 99%
“…Although there was no significant relationship between age and infection, several surveys have emphasized that dogs less than one year old were most likely to be infected with Campylobacter. 2,16,22,[24][25][26]32 It may be because of the weakness of the puppies and the low level of immunity in young dogs compared to adults. 22,30 Although Campylobacter was more prevalent in male compared to female dogs, the statistical analysis showed no significant difference, implying that Campylobacter exposure has no gender predilection in dogs, which is consistent with the results of a previous study.…”
Section: Discussionmentioning
confidence: 99%